2022
DOI: 10.3390/foods11040577
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of p-Coumaric Acid on Browning Inhibition in Potato Polyphenol Oxidase-Catalyzed Reaction Mixtures

Abstract: There has been considerable interest in using natural polyphenol oxidase (PPO) inhibitors to control browning in fruit and vegetable products. p-Coumaric acid (pCA), a common secondary metabolite of plants, has been studied as an inhibitor of PPOs/tyrosinases from several foods (e.g., mushroom, apple, and potato). However, studies on the use of pCA for the inhibition of PPO-initiated browning in actual food systems are limited. Therefore, a study was carried out to ascertain the efficacy of using pCA to limit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…For the antidiabetic enzymes, syringic and p -coumaric acids exhibited a linear correlation between these enzyme inhibitions. In general, p -coumaric and syringic acids were main contributors to the tested enzyme inhibition and have reported as potent inhibitors in previous studies. …”
Section: Resultsmentioning
confidence: 66%
“…For the antidiabetic enzymes, syringic and p -coumaric acids exhibited a linear correlation between these enzyme inhibitions. In general, p -coumaric and syringic acids were main contributors to the tested enzyme inhibition and have reported as potent inhibitors in previous studies. …”
Section: Resultsmentioning
confidence: 66%
“…The phenolics in various plant extracts play a major role in the browning inhibition of fresh-cut fruit and vegetables (Zhang et al, 2022). It has been reported that phenolic treatments show strong inhibitions on fresh-cut product browning (Jiang and Penner, 2022).…”
Section: Discussionmentioning
confidence: 99%